PENGARUH PENGETAHUAN DAN PEMAHAMAN PERATURAN PERPAJAKAN, PENGHINDARAN PAJAK DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK (Studi Pada Wajib Pajak Orang Pribadi di Wilayah KPP Pratama Kota Tegal) - Febri, Davidya; Sulistyani, Tri (PERMANA, 2018)
The purpose of this study was to determine the effect of knowledge and understanding of taxation regulations, tax avoidance and taxation sanctions simultaneously and partially on taxpayer compliance. To find out the difference in knowledge and understanding of taxation regulations,  tax  avoidance,  taxation  and  compliance  sanctions  on  private  taxpayers  of private employees with ASN's personal taxpayers. In this study using the population of all individual taxpayers registered in the Tegal City KPP with a sample of 100 respondents. The sampling technique using simple random sampling. Methods of data collection by distributing questionnaires. The data is processed using SPSS program version 23. The results of this study conclude that the first hypothesis is that there is the influence of knowledge and understanding of tax regulations, tax avoidance and taxation sanctions simultaneously on taxpayer compliance with a significant value of 0,000. The second hypothesis  is  that  there  is  an  influence  of  knowledge  and  understanding  of  taxation regulation partially to taxpayer compliance with the significant value equal to 0,011. The third hypothesis is that there is no partial tax avoidance effect on taxpayer compliance with a significant value of 0.069. The fourth hypothesis is that there is a partial effect of taxation sanctions on taxpayer compliance with a significant value of 0.030. The fifth hypothesis is that  there  are  differences  in  knowledge  and  understanding  of  taxation  regulations,  tax evasion,  tax  sanctions  and  compliance  with  private  taxpayers  private  employees  with taxpayers personal ASN. While for both groups of taxpayers both private and ASN employees do not differ or there is no difference in preferences on tax sanctions.Keywords: knowledge and understanding of taxation regulations, tax avoidance, taxation sanctions and taxpayer compliance.